A study on the communication and dissemination element of early warning systems in the Municipality of Oras, Eastern Samar - Abit, Kent Eugene O.; Veloso, Keith James V.; Lim, Ladylyn B. (2015)
Early Warning Systems are rooted in the goal to save lives and lessen possible damages through the dissemination of warnings and the constant surveillance of the upcoming disaster. During the devastation of Super Typhoon Haiyan, locally known as Yolanda, numerous casualties and damaged to destroyed properties were incurred. The narratives of some survivors avowed that aside from the strength of the said super typhoon, the lack of proper warning dissemination greatly contributed to the visible aftermath. A year later after Haiyan, Eastern Visayas was struck again by an almost similar typhoon known as Hagupit, locally identified as Typhoon Ruby. Under this circumstance, zero casualties were recorded. This research focused on the third element of Early Warning Systems which is the Warning Dissemination and Communication element in the Municipality of Oras, Eastern Samar-- the neighboring municipality of Dolores, Eastern Samar which was the center of Typhoon Ruby. This study also made use of the indicators presented by UNU-EHS and OCHA as guidelines of good warning dissemination along with John Twigg's assertion that communication to the public is the core to disaster and risk reduction. Lastly, this research paper delved into the factors that hinder or promote warning dissemination and the communication processes in pre-disaster instances in the lens of both municipal and barangay level.
Results gathered through qualitative interviews depict that the bandilyo system- the process of disseminating information through word of mouth is the major means of communication and warning dissemination. The results further showed that the flow of information follows a waterfall process as information is mainly concentrated in the officials of both the barangay and municipal level. The indicators presented by UNU-EHS and OCHA such as the ability to reach the vulnerable population, the understability of warnings and the relevance and usefulness of the information included in the warnings was successfully achieved. Facilities are limited but the bandilyo system is able to serve its purpose.
Undergraduate thesis (B.A.S.S. Political Science)-- Univeristy of the Philippines, Tacloban.